Território Vulnerável e Desenvolvimento Humano. Uma Análise à Luz da Política Pública de Assistência social - Alex Pizzio (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2016)
The fight against inequality and poverty has been the subject of both public policy and the development models that give them support. In contemporary Brazil, descentralisation of social services, priority policy in mitiganting poverty and inequality, has considered, the territory as a strategic dimension to the success of the policy through the improvement of themanagement and provision of public services. The purpose of this article is to reflect on the circumstances involvingindividuals, the spaces and the human development perspective in order to understand the complexity of the territoryagainst the Social Assistance policy contexts. To realize this goal, we speak about the socio-economic, civil and territorialvulnerability, seeking to define the main characteristics of the territory vulnerable and, thereby, contribute to the deepeningof the research on the territorialization of public policy of social assistance and human development. The findings show that the territories considered vulnerable require best ways for the implementation, management, monitoring, evaluationand information within the framework of social welfare policy, so as to overcome the traditional perspective to focus on the individual and the condition of poverty.